Materials selection guidelines for geothermal energy utilization systems - Ellis, P. F., II; Conover, M. F. (Radian Corporation, 1981)
This manual includes geothermal fluid chemistry, corrosion test data, and materials operating experience. Systems using geothermal energy in El Salvador, Iceland, Italy, Japan, Mexico, New Zealand, and the United States are described. The manual provides materials selection guidelines for surface equipment of future geothermal energy systems. The key chemical species that are significant in determining corrosiveness of geothermal fluids are identified. The utilization modes of geothermal energy are defined as well as the various physical fluid parameters that affect corrosiveness. Both detailed and summarized results of materials performance tests and applicable operating experiences from forty sites throughout the world are presented. The application of various non-metal materials in geothermal environments are discussed. Included in appendices are: corrosion behavior of specific alloy classes in geothermal fluids, corrosion in seawater desalination plants, worldwide geothermal power production, DOE-sponsored utilization projects, plant availability, relative costs of alloys, and composition of alloys. (MHR)